An Appraisal of the Establishment, Influence, and Growth Trajectories of Five Nigerian Pentecostal Churches - Odion, Omogbai Ehimikhuae (Advances in Social Sciences Research Journal, 2025)
This article examines the establishment and development of five prominent Nigerian Pentecostal churches with the aim of understanding the trajectories for their role, contributions, and impact as spiritual entities and social force on contemporary Christianity in the lives of Nigerians and on Nigeria’s national development. With the use of a multiple case study design methodology, supported by narrative techniques that are historical, sociological, and ethnographic, relevant data was drawn from available scholarly literature with other published and unpublished materials. The article examines the Deeper Life Bible Church, the Redeemed Christian Church of God, the Living Faith Church Worldwide, Mountain of Fire and Miracles Ministries, and Daystar Christian Centre as case studies. The five churches are each analyzed in relation to their foundational vision, mission, strategies for evangelism, missions, and church planting operations including their responses to shifting socio-cultural, economic, and political environment of Nigeria, home and abroad. The article argues that the emergence, growth, and development of Pentecostal churches in Nigeria are not simply a religious phenomenon, but a reflection of the interplay of dynamic leadership, innovativeness, and socio-economic aspirations that these churches strategically adapt to the ongoing dynamic situations in Nigeria. The resultant effect of this article is that it contributes to the general discourse on Pentecostalism from the prism of Nigeria as it reveals how their involvement in both local and global dynamics have shaped the growth, development and influence of these five Pentecostal churches.